The Principle of Utmost Good Faith in the Rejection of Life Insurance Claims Based on Pre-Existing Conditions: An Analysis of Medan District Court Decision No. 743/Pdt.G/2024/PN.Mdn - Wiwin Windiantina Wintarsih; Riksa Arwin Aliasanti (Fakultas Hukum Universitas Lampung, 2026)
The principle of utmost good faith requires both parties in insurance agreement to disclose all material facts relevant to the insured risk. Disputes often arise when insurers reject life insurance claims based on alleged non-disclosure of pre-existing conditions. This study examines the application of the utmost good faith principle under Law No. 40 of 2014 on Insurance and analyzes the legal reasoning in Medan District Court Decision No. 743/Pdt.G/2024/PN.Mdn. Using a normative juridical method with statutory and case approaches, the study finds that claim rejection is justified only if the insurer proves that the insured failed to disclose a material fact that affected the underwriting decision. A pre-existing condition alone is insufficient without proof of its materiality, its causal relationship to risk acceptance, and compliance with a professional underwriting process. The study proposes a reconstructed model of the utmost good faith principle based on balanced legal protection, treating disclosure obligations, the burden of proof, and underwriting responsibilities as reciprocal duties of the insurer and the insured. This model advances existing scholarship by providing a more balanced framework for resolving life insurance claim disputes involving pre-existing conditions.